2020
DOI: 10.1177/0003319720921741
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Men Invited to Participate in a Population-Based Abdominal Aortic Aneurysm Screening Program

Abstract: A screening program for abdominal aortic aneurysm (AAA), inviting 65-year-old men, was started in Stockholm in 2010 (2.3 million inhabitants). The aim was to present a long-term follow-up of men participating in screening, as well as AAA repair and ruptures among nonparticipants. Demographics were collected for men with screening detected with AAA 2010 to 2016 (n = 672) and a control group with normal aortas at screening (controls, n = 237). Medical charts and regional Swedvasc (Swedish Vascular regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…1 In contrast, patients not participating in the screening program had a >30-fold higher AAA rupture rate (0.096%; P < .001). 1 The usefulness of AAA screening programs is much debated. Some authors support that population-wide AAA screening programs are necessary and effective, [2][3][4] whereas others argue that these programs cause more harm than good.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…1 In contrast, patients not participating in the screening program had a >30-fold higher AAA rupture rate (0.096%; P < .001). 1 The usefulness of AAA screening programs is much debated. Some authors support that population-wide AAA screening programs are necessary and effective, [2][3][4] whereas others argue that these programs cause more harm than good.…”
mentioning
confidence: 92%
“…11 Similarly, Hultgren et al reported that 82.9% of their AAA patients died from a non-AAA-related cause. 1 Thus, recognizing the presence of an AAA and treating it as a coronary heart disease equivalent may save more lives than just by dealing with AAAs.…”
mentioning
confidence: 99%
See 3 more Smart Citations